Characteristics and course of patients treated with Kampo Medicine in the Department of General Medicine. (21st February 2020) - Takayama, Shin; Akaishi, Tetsuya; Nozaki, Hiroyuki; Suzuki, Satoko; Arita, Ryutaro; Saito, Natsumi; Tanaka, Junichi; Numata, Takehiro; Kikuchi, Akiko; Ohsawa, Minoru; Abe, Michiaki; Ishii, Tadashi
Abstract: Background: A recent investigation reported that 92.7% Japanese family physicians have prescribed Kampo medicine (KM). KM can treat a wide variety of conditions from mental disorders to physical weaknesses. However, the characteristics and course of patients treated with KM at the Department of General Medicine remain unclear. Aims: To investigate the characteristics and course of patients treated with KM in our hospital. Methods: Data on medical history, complaints, course after Kampo treatment, and Hamilton Depression Rating Scale (HAM‐D) scores were retrogradely collected. The background of patients who received Kampo treatment was compared to that of patients who did not. Result: Of 362 patients, 51 were treated with KM. Symptoms for which KM was prescribed included pain, general malaise, or sensory disturbance of extremities. All patients treated with KM were screened and initially diagnosed with a functional disorder or noncritical condition. KM including a crude drug of saiko such as hochuekkito, shigyakusan, shosaikoto, and yokukansan, was frequently prescribed for patients. Subjective symptoms showed improvement (53%) and no change (47%), while worsening was not observed in any patient. HAM‐D scores showed that patients treated with KM had higher anxiety levels and related symptoms as well as a higher frequency of mental disorders prior to presenting at the hospital. Conclusion: Most complaints of the patients treated with KM were pain, general malaise, and sensory disturbance. KM is more likely to be prescribed in patients with health‐related anxiety or a history of mental disorders. Abstract : Kampo medicine is more likely to be prescribed in patients with health‐related anxiety or a history of mental disorders who visit the Department of General Medicine.